Effect of Cytochrome P450 (CYP) 2D6 Genetic Polymorphism on the Inhibitory Action of Antidepressants on CYP2D6-Mediated Dopamine Formation from p-Tyramine - Toshiro Niwa; Mayumi Yanai; Maya Matsumoto; Marina Shizuku (Frontiers Media S.A., 2018)
PURPOSE: The inhibitory effects of antidepressants, such as imipramine, desipramine, and fluvoxamine, on dopamine formation from p-tyramine catalyzed by cytochrome P450 (CYP) 2D6.2 (Arg296Cys, Ser486Thr) and CYP2D6.10 (Pro34Ser, Ser486Thr), were compared with those on dopamine formation catalyzed by CYP2D6.1 (wild type), to investigate the effect of a CYP2D6 polymorphism on neuroactive amine metabolism in the brain. METHODS: Inhibition constants (Ki) of the antidepressants toward dopamine formation catalyzed by CYP2D6.1, CYP2D6.2, and CYP2D6.10, which were expressed in recombinant Escherichia coli, were compared. RESULTS: Imipramine and desipramine competitively or non-competitively inhibited dopamine formation mediated by CYP2D6.1, CYP2D6.2, and CYP2D6.10 with Ki values of 3.9-4.9, 5.9-9.6, and 26.7-37.5 µM, respectively. The maximal velocity (Vmax) values for dopamine formation by all CYP2D6 variants gradually increased with increasing fluvoxamine concentrations up to 40-100 µM, indicating that fluvoxamine stimulated dopamine formation. CONCLUSIONS: These results suggest that the inhibition/stimulation of CYP2D6-mediated dopamine formation by these antidepressants would be affected by CYP2D6 polymorphism in the brain.   This article is open to POST-PUBLICATION REVIEW. Registered readers (see "For Readers") may comment by clicking on ABSTRACT on the issue's contents page.